1994
DOI: 10.1017/s0950268800057435
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of aerosol and intragastric routes of infection withListeriaspp

Abstract: SUMMARYAerosol infection (Al) of Porton outbred mice with Listeria species, exhibiting varying degrees of virulence, was compared with gastric intubation (GI) on the basis of numbers of deaths, 50% lethal dose (LD50) and pattern of listerial infection. The Al route appeared to be more sensitive, efficient and consistent than GI in that it required 105 fewer micro-organisms to obtain infection and death then ensued within 4 days, with GI deaths usually occurring on day 7. All the virulent strains tested caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…typhimurium are required to produce disease in mice when given as an aerosol (Wathes et al 1988). It has also been reported that aerosol infection of mice with selected species of listeria required 10' fewer organisms (than the oral route) to produce infection (Bracegirdle et al 1994). Given the low levels of airborne salmonella in this experiment, chicks are clearly more susceptible to salmonella infection by the aerosol route than mice.…”
Section: Discussionmentioning
confidence: 62%
“…typhimurium are required to produce disease in mice when given as an aerosol (Wathes et al 1988). It has also been reported that aerosol infection of mice with selected species of listeria required 10' fewer organisms (than the oral route) to produce infection (Bracegirdle et al 1994). Given the low levels of airborne salmonella in this experiment, chicks are clearly more susceptible to salmonella infection by the aerosol route than mice.…”
Section: Discussionmentioning
confidence: 62%
“…Listeria monocytogenes has been found in 10% or more of normal healthy people, usually in the gut (Anon 2005). All the 13 serovars of L. monocytogenes are reported to cause human listeriosis, but serovars 1/2a, 1/2b and 4b are implicated with most of the cases (Bracegirdle et al. 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to typical foodborne pathogens like Salmonella spp., which seldom result in fatalities, listeriosis is now known to have a staggering fatality rate of up to 30% [78]. The common serotypes linked to human listeriosis include 1/2a, 1/2b, and 4b [80]. Since the placenta acts as a breeding ground for LM, pregnant women are more susceptible to infection.…”
Section: Lm Infectionmentioning
confidence: 99%